2017
DOI: 10.1002/ccd.26963
|View full text |Cite
|
Sign up to set email alerts
|

Ratio of systolic blood pressure to left ventricular end‐diastolic pressure at the time of primary percutaneous coronary intervention predicts in‐hospital mortality in patients with ST‐elevation myocardial infarction

Abstract: An SBP/LVEDP ratio ≤ 4 identified a group of STEMI patients at high risk of in-hospital death. © 2017 Wiley Periodicals, Inc.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
21
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 28 publications
3
21
0
Order By: Relevance
“…El‐Menyar et al found that a PP ≤30 mm Hg was associated with excess mortality in a study of more than 2,500 patients with STEMI . We previously reported that an SBP/LVEDP ratio ≤4 greatly increased the risk of in‐hospital mortality in STEMI patients undergoing PPCI and Tesak et al found that SBP/LVEDP predicted 30‐day mortality in STEMI patients with an optimal cut‐off of 4.4 . The present study provides insight into these findings by demonstrating that LVEDP, PP, and SBP/LVEDP ratio correlate with the size of infarction in STEMI patients.…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…El‐Menyar et al found that a PP ≤30 mm Hg was associated with excess mortality in a study of more than 2,500 patients with STEMI . We previously reported that an SBP/LVEDP ratio ≤4 greatly increased the risk of in‐hospital mortality in STEMI patients undergoing PPCI and Tesak et al found that SBP/LVEDP predicted 30‐day mortality in STEMI patients with an optimal cut‐off of 4.4 . The present study provides insight into these findings by demonstrating that LVEDP, PP, and SBP/LVEDP ratio correlate with the size of infarction in STEMI patients.…”
Section: Discussionsupporting
confidence: 68%
“…Cardiogenic shock is characterized by increased sympathetic tone and activation of compensatory mechanisms leading to increased heart rate, augmented LV contractility, fluid retention and vasoconstriction, all of which can increase SBP. There is accumulating data that hemodynamic measurements such as left ventricular end‐diastolic pressure (LVEDP), pulse pressure (PP), and SBP/LVEDP ratio measured at the time of PPCI are more predictive of outcomes in STEMI patients than SBP and thus might have a better correlation with the amount of the left ventricle impacted by a myocardial infarction . Therefore, the objectives of this study were to identify invasive hemodynamic parameters measured at the time of PPCI that best correlate with the size of infarction as defined by peak troponin I levels and LVEF measured by echocardiography during hospitalization.…”
Section: Introductionmentioning
confidence: 99%
“…Sola et al, in their single centre retrospective analysis of 219 STEMI patients, showed that a systolic blood pressure to LVEDP ratio ≤ 4 identi ed the group of STEMI patients at high risk of in-hospital death. (18) Similarly, in an analysis of 1283 STEMI patients, Ndrepepa et al demonstrated that a lower LVEF/LVEDP ratio was independently associated with increased risk of cardiac mortality up to 8 years after primary PCI. (19) The LVEF/LVEDP ratio, but not LVEF or LVEDP alone, improved predictive accuracy of multivariable models with respect to long-term cardiac mortality.…”
Section: Discussionmentioning
confidence: 95%
“…These cut points were chosen given the high prevalence of primarily Stage D patients, 14 with severely abnormal myocardial structure and function. Other measurements used were the ratio of systolic blood pressure (SBP) to PCWP, stratified above and below four 15 and cardiac power index (CPI; {[mean arterial pressure (mmHg) × cardiac output (L/min/m 2 )] × [0.0022]}/[body surface area (m 2 )], stratified above and below the median 16 . Pulmonary artery pulsatility index ([pulmonary artery systolic pressure ‐ pulmonary artery diastolic pressure]/[right atrial pressure]; PAPi) was calculated, stratified above and below the median, and correlated to LA levels 17,18 …”
Section: Methodsmentioning
confidence: 99%